1986
DOI: 10.1017/s004317450006793x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Adjuvants and Environment During Plant Development on Glyphosate Absorption and Translocation in Field Bindweed (Convolvulus arvensis)

Abstract: Absorption and translocation of glyphosate [N-(phosphonomethyl)glycine] with and without adjuvants were examined in field bindweed (Convolvulus arvensisL. # CONAR) to develop an understanding of the influence of selected adjuvants and environment before application on glyphosate activity. Light intensity and humidity during plant development resulted in differences in14C-glyphosate absorption. When applied in water or with an oxysorbic (20 POE) (polyoxyethylene sorbitan monolaurate) adjuvant, an average of 9% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0
2

Year Published

1991
1991
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 18 publications
(20 reference statements)
6
63
0
2
Order By: Relevance
“…The leaves of higher plants are covered by a cuticle, that is, an extracellular membrane that usually is considered as the main barrier against foliar absorption (Bukovac 1976). Sherrick et al. (1986) investigated the effects of adjuvants and the environment during plant development on the level of glyphosate absorption and translocation in field bindweed ( C. arvensis L.) and confirmed that the thickness of the cuticle of bindweed leaves affects the herbicide's level of efficacy.…”
Section: Discussionmentioning
confidence: 93%
“…The leaves of higher plants are covered by a cuticle, that is, an extracellular membrane that usually is considered as the main barrier against foliar absorption (Bukovac 1976). Sherrick et al. (1986) investigated the effects of adjuvants and the environment during plant development on the level of glyphosate absorption and translocation in field bindweed ( C. arvensis L.) and confirmed that the thickness of the cuticle of bindweed leaves affects the herbicide's level of efficacy.…”
Section: Discussionmentioning
confidence: 93%
“…Translocation mirrored absorption (Fig 6b). Similarly, in field bindweed ( Convolvulus arvensis L) glyphosate absorption was increased two‐to three‐fold with MON 0818 compared to no adjuvant; reductions in the concentration of MON 0818 lowered necrosis and resulted in increased movement of radioactivity away from the site of application 12…”
Section: Discussionmentioning
confidence: 99%
“…The effect of adjuvants on absorption and translocation of glyphosate has been examined by several workers 8–11. Sherrick et al 12 reported that absorption of [ 14 C]glyphosate was increased two‐ to three‐fold by incorporation of a polyethoxylated tallow amine surfactant (MON 0818). Reduction in surfactant concentrations below 10 g litre −1 caused less initial necrosis and resulted in increased translocation of [ 14 C]glyphosate from the site of application.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the addition of either surfactant series, a significantly higher absorption of the 14 C‐glyphosate was recorded by both weed species. Sherrick et al. (1986) reported a two‐to‐three‐fold increase in the absorption of glyphosate with a polyethoxylated TA adjuvant.…”
Section: Resultsmentioning
confidence: 99%